Land use competition in Sub-Saharan Africa's rural areas - Kerstin Nolte; Kacana Sipangule (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2017)
There has been an increased interest in agricultural land in Africa's rural areas. While foreign investments have taken center stage in the debate on large-scale agricultural investments, the role played by domestic investors - particularly medium-scale farmers - should not be neglected. This interest in agricultural land further increases land pressure and land use competition between commercial interests, local livelihoods and ecosystem services. Land poor smallholders and pastoralists are the most vulnerable in this transformation; both are challenged by a loss of access to land and increased competition on local markets. Policy needs to focus on raising smallholder agricultural productivity and on exploiting the potential for smallholders.
Keywords: 330